2013
DOI: 10.1111/aor.12182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Pulsatile and Nonpulsatile Flow on Plasma Fibrinolytic Balance in Pediatric Patients Undergoing Cardiopulmonary Bypass

Abstract: In the brain, the components of the fibrinolytic system, tissue plasminogen activator (tPA) and its endogenous inhibitor plasminogen activator inhibitor-1 (PAI-1), regulate various neurophysiological and pathological responses. Fibrinolytic balance depends on PAI-1 and tPA concentrations. The objective of this study is to compare the effects of pulsatile and nonpulsatile perfusion on fibrinolytic balance in children undergoing pediatric cardiopulmonary bypass (CPB). Plasma PAI-1 antigen and tPA antigen were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…There is mounting evidence that pulsatile flow may reduce some of the complications related to extracorporeal circulation by improving vital organ microcirculation and reducing the need for inotropes (7)(8)(9). Multiple studies of cardiopulmonary bypass and ventricular assist device support have shown the benefits of pulsatile flow (10)(11)(12)(13)(14)(15). Synchronizing pulsatile ECLS to the patient's intrinsic rhythm may have additional clinical benefit as the delivered pulsatility would not compete with the patient's intrinsic cardiac systolic performance.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that pulsatile flow may reduce some of the complications related to extracorporeal circulation by improving vital organ microcirculation and reducing the need for inotropes (7)(8)(9). Multiple studies of cardiopulmonary bypass and ventricular assist device support have shown the benefits of pulsatile flow (10)(11)(12)(13)(14)(15). Synchronizing pulsatile ECLS to the patient's intrinsic rhythm may have additional clinical benefit as the delivered pulsatility would not compete with the patient's intrinsic cardiac systolic performance.…”
Section: Discussionmentioning
confidence: 99%
“…15 This raises concerns for the comparability of TEG to T-TAS, as dilution and variance in viscosity complicate differences between the stagnant and flow conditions. 40,41 Another limitation of our study is the inherent qualitative difference of the LY30 metric in relation to T-TAS’s settings for both PL and AR chips. In TEG, LY30 is a measurement obtained after MA is reached, but T-TAS stops running its assay before an MA or LY30 equivalent is measured as T-TAS’s design includes a preset pressure ceiling to stop running the assay at ~80 kPa for the AR chip and ~60 kPa for the PL chip.…”
Section: Discussionmentioning
confidence: 97%
“…tPA and PAI-1 regulate various neurophysiological and pathological responses in the brain. In a prospective study, we compared the effects of pulsatile and nonpulsatile perfusion on tPA and PAI-1 levels in 40 children undergoing CPB, and found that the pulsatile group had lower PAI-1 levels and PAI-1 : tPA molar ratios at 24 h following CPB procedure (27). The results suggest that pulsatile flow maintains endogenous fibrinolytic balance after pediatric CPB.…”
Section: Plasma Fibrinolytic Balancementioning
confidence: 92%
“…In a prospective study, we compared the effects of pulsatile and nonpulsatile perfusion on tPA and PAI-1 levels in 40 children undergoing CPB, and found that the pulsatile group had lower PAI-1 levels and PAI-1 : tPA molar ratios at 24 h following CPB procedure (27). tPA and PAI-1 regulate various neurophysiological and pathological responses in the brain.…”
Section: Plasma Fibrinolytic Balancementioning
confidence: 99%